Current questions of EU VAT grouping. (2nd January 2015) - Pfeiffer, Sebastian
Abstract : EU VAT grouping as an optional provision for the Member States of the European Union gives rise to several questions regarding its interpretation. In the article, the author analyses the current question of the EU VAT grouping notion which either have been controversially discussed throughout academic literature or have been brought up after the recent CJEU case law. While VAT grouping may be a means to facilitate VAT neutrality, the current EU provisions lead to disparities particularly in cross-border situations. Without further harmonisation, the potential of VAT grouping cannot be fully utilised and may lead to the eventual abolishment of VAT grouping.